Pemberdayaan Pelaku UMKM Sektor Kuliner Desa Cibeber dengan Kualitas Produk dan Teknik Pengolahan Makanan - Aditya, Michael Khrisna; Taviprawati, Ervina; Putriana, Nur Fitria; Junandar, Dwi Rifki (Jurnal Pemberdayaan Pariwisata, 2025)
The aim of this community service is to improve the product quality of business owners in Cibeber Tourism Village, Purwakarta, through training and counseling on the application of safe and hygienic processing standards. The methods used in this activity include an initial survey, counseling on the importance of product quality, and training on raw material processing techniques and packaging that meet standards. The results of the activity show an increase in the knowledge and skills of business owners in producing safer, more hygienic products with higher market value. Additionally, the application of the taught techniques successfully improved the food product quality in the village. As a recommendation, periodic evaluations should be conducted to ensure the sustainability of the processing standards, as well as strengthening product marketing so that business owners can compete more effectively in a broader market . Keywords: product quality, food processing counseling